Virtual Screening of Potential Inhibitors against the Penicillin-Binding Protein 1a (PBP1a) of Streptococcus pneumoniae - Shehzad, Adnan; Farkhanda; Zainab, Shah; Yasmin, Samina; Inam Ullah; Khan, Kashif; Saif Ullah; Ayesha, Bibi; Hamid Ur Rahman (Indus Journal of Bioscience Research, 2025)
Background: Pneumonia is an inflammatory condition of the lungs caused by the bacterium Streptococcus pneumoniae. It is a significant cause of mortality and morbidity, particularly among young children, adults and immunocompromised persons. Resistance against drugs is continuously evolving in nearly all pathogens. The constant need for alternative therapeutic options demands the necessity of an ongoing search for novel drugs. Objective: The current study was thus designed to target the penicillin binding protein of Streptococcus pneumoniae (PBP1a), a protein involved in critical cellular and metabolic processes. Method: PBP1a sequence of Streptococcus pneumoniae was obtained from UniProt database and protein BLAST was performed. 3D structure of PBP1a was downloaded from RCSB and visualized using Discovery Studio Visualizer. 150 drugs were docked using PatchDock web server and protein interactions were explored using GS Viewer, LigPlot+ and Discovery Studio Visualizer. Result: Out of the 150 drugs chosen, Lamivudine, Dolutegravir and Loperamide showed the most interactions with Streptococcus pneumoniae PBP1a. These interactions included covalent bonds, hydrogen bonds and hydrophobic interactions. Conclusion: The drugs Lamivudine, Dolutegravir and Loperamide interacted uniquely with the target protein. These interactions may trigger metabolic changes and could inhibit the growth and kill the parasite. Further experimental study is needed to fully understand the potential of these drugs.